Biometric image discrimination technologies - Zhang, David 1949-; Jing, Xiaoyuan; Yang, Jian (Computational intelligence and its applications series, 2006)
The book gives an introduction to basic biometric image discrimination technologies including theories that are the foundations of those technologies and new algorithms for biometrics authentication"--Provided by publisher